FRI0401 Eosinophilic fasciitis (EF) clinical characteristics and response to mtx therapy. (23rd January 2014) - Berianu, F.; Cohen, M. D.; Abril, A.; Ginsburg, W. W.
Abstract : Background: The treatment of EF is still a challenge for rheumatologists. Objectives: To report our experience with fourteen EF patients on MTX followed over a period of 1 to 14 years in the rheumatology clinic. Methods: Chart reviews of the patients with biopsy proven EF treated with MTX 15-20 mg/week from 1998-2012. Results: There were 6 women and 8 men, aged 30 to 75 (mean age 52). None had used tryptophan. All patients had clinical induration of the arms and legs. Six had truncal involvement, seven had abdominal wall involvement and none had Raynaud's. Eight patients had localized morphea. One patient had clinical evidence of EF involvement limited to the left side of the body but MRI showed bilateral fascial involvement of the extremities. Eleven patients were started on MTX therapy either after a trial of Prednisone or combination immunosupressive therapy. Two patients were simultaneously started on MTX and Prednisone. One patient was started on MTX alone. Three patients had been treated initially with Hydroxychloroquine/Prednisone therapy and two with Azathioprine/Prednisone without any further benefit after the partial improvement with steroids. Eleven patients were able to taper off Prednisone within 10 to 33 months (mean 16.5 months). After initiation of the MTX therapy nine patients achieved complete clinical remission within 12 months to 7 years of therapy (mean 32.3 months). Three patients maintained remission and are off all medications at 1 to 3 years of follow up. One patient is in complete clinical remission still on low dose MTX. Five patients had relapses of the disease while off MTX therapy within 7 months to 3 years (mean 24.2 months). All of relapses responded well to restarting MTX therapy and two of these patients achieved a second remission on additional MTX therapy within 18 months to 5 years. Four patients had partial remission on MTX 3-5 years after initiation of therapy. One patient had only a minimal response to MTX after 4 years of therapy. Conclusions: The majority of patients (13 out of 14) had improvement on the MTX/Prednisone therapy; Eleven patients were able to taper off steroids; Nine patients achieved complete remission. We believe that MTX represents an effective treatment option for EF. References: Eosinophilic fasciitis: clinical spectrum and therapeutic response in 52 cases. Lakhanpal S, Ginsburg WW, Michet CJ, Doyle JA, Moore SB, Semin Arthritis Rheum. 1988;17(4):221 Eosinophilic fasciitis (Shulman disease): new insights into the therapeutic management from a series of 34 patients. Lebeaux D, Francès C, Barete S, Wechsler B, Dubourg O, Renoux J, Maisonobe T, Benveniste O, GatfosséM, Bourgeois P, Amoura Z, Cacoub P, Piette JC, Sène D; Rheumatology (Oxford). 2012 Mar;51(3):557-61. Epub 2011 Disclosure of Interest: None Declared